Fumonisin and ochratoxin-producing strains of Aspergillus section Nigri are associated with onion (Allium cepa L.) bulbs sold in markets in southwest Nigeria - Esuola, C.O.; Ortega-Beltran, A. (Frontiers Media, 2025)
Introduction: Onion bulbs are edible, nutritious vegetables and spices. In Nigeria, mass propagation of onion seedlings is limited due to infection of the onion bulbs by Aspergillus section Nigri, especially Aspergillus niger strains. Mycotoxin-producing A. niger strains are detrimental to public health. Hence, this study was undertaken to screen the locally sourced onion bulbs for fumonisin B2 (FB2) [Multiplex A: fum6 (374 bp), fum8 (272 bp), fum13 (168 bp), and fum19 (479 bp) and Multiplex B: fum1 (452 bp), fum7 (238 bp), fum3 (173 bp), and fum14 (321 bp)] and ochratoxin A [OTA; pks15ks (776 bp)] A. niger biosynthetic genes.